The Participation of Human Reseources in Albanian Local Governance Obligates - Papajorgji, Zhyljen; Dumi, Alba; Gjika, Irma (Mediterranean Journal of Social Sciences, 2012)
The role of the Human Resources Management in organizations has grown exponentially over the last decade. Specializedprofessional training, such as certification, is critical for those practicing in the Human Resource field, in order to keep pace with thedemands of the industry. Democratic Albanian local governance is a prerequisite to the meaningful decentralization of infrastructuremanagement. When people participate in defining visions for sustainable development of HRM for their communities, in formulatingstrategies for equitable access to services and resources and in setting priorities for action, they have endorsed. Participation alsosharpens their awareness of the interrelations between economic, social and environment issues. This is a highly significant feature ofinfrastructure Albanian programs and carries important implications for local development. Decentralization on HRM has given localgovernments the discretion and scope they need to take a lead role in responding to the challenges of economic downturn, degradationof the urban environment, and social hardship. They institute bold initiatives and innovative practices.